How Kelon and Haier innovated to attract the local Chinese market - Shen, Xiaobai (Henry Stewart Talks, 2017)
The case study looks at locally developed washing machines in rural China that wash both food and clothing as an example of Chinese aptitude in innovating products that best fit the needs of target consumers.